2010
DOI: 10.1164/rccm.200812-1902oc
|View full text |Cite
|
Sign up to set email alerts
|

Differential Expression of Tissue Repair Genes in the Pathogenesis of Chronic Obstructive Pulmonary Disease

Abstract: Rationale: The airflow limitation that defines severity of chronic obstructive pulmonary disease (COPD) is caused by a combination of small airway obstruction and emphysematous lung destruction. Objectives: To examine the hypothesis that small airway obstructive and emphysematous destructive lesions are produced by differential expression of genes associated with tissue repair. Methods: The expression of 54 genes associated with repair of repetitively damaged tissue was measured in 136 paired samples of small … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

9
100
1
4

Year Published

2011
2011
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 134 publications
(114 citation statements)
references
References 48 publications
9
100
1
4
Order By: Relevance
“…We observed a novel association of TNF-a induced MMP9 mRNA expression with FEV1 % pred (table 3). This observation is consistent with previous data that demonstrated MMP9 expression increased in the lung parenchyma surrounding small airways as FEV1 % pred decreased [40]. There is also supportive evidence that MMP9 contributes to the development of emphysema from mouse models [41,42].…”
Section: Discussionsupporting
confidence: 93%
See 1 more Smart Citation
“…We observed a novel association of TNF-a induced MMP9 mRNA expression with FEV1 % pred (table 3). This observation is consistent with previous data that demonstrated MMP9 expression increased in the lung parenchyma surrounding small airways as FEV1 % pred decreased [40]. There is also supportive evidence that MMP9 contributes to the development of emphysema from mouse models [41,42].…”
Section: Discussionsupporting
confidence: 93%
“…There is also supportive evidence that MMP9 contributes to the development of emphysema from mouse models [41,42]. Our data suggest that it is the level of MMP9 in response to specific pro-inflammatory stimuli that plays a critical role in the development of COPD, in agreement with studies showing that increases in TNF-a are associated with reductions in lung function [40] and that TNF-a plays an important role in cigarette smoke-induced emphysema [43].…”
Section: Discussionsupporting
confidence: 90%
“…32 Thus, it is plausible that genetic variants in SERPINE2 infl uence asthma and COPD through modulation of airway remodeling processes.…”
Section: Discussionmentioning
confidence: 99%
“…LAPAN et al [50] pointed out that MMP-12 levels in induced sputum tend to be relatively low and developed highly specific assays to detect it; they were able to find MMP-12, but could not identify differences between control and COPD patients. GOSSELINK et al [51] could not find any associations with parenchymal MMP-12 gene expression and Global Initiative for Chronic Obstructive Lung Disease (GOLD) stage. LEE et al [52] investigated the potential association of single nucleotide polymorphisms (SNPs) in MMP-1, MMP-9 and MMP-12 with COPD in a Korean population and found that only the MMP-9 -1562CRT showed a (protective) correlation; the MMP-12 N357S SNP was not associated with differences in COPD frequency.…”
Section: Does Mmp-12 Participate In Human Copd?mentioning
confidence: 95%